Revisiting the region of the open cluster NGC 5606 - Orsatti, Ana María (2007)
We present polarimetric observations in the UBVRI bands corresponding to 54 stars located in the direction of NGC 5606. Our intention is to analyze the dust characteristics between the Sun and the cluster, as well as to confirm doubtful memberships using Polarimetrie tools. We also want to determine if a group of 11 B and A stars identified in the past by Vázquez & Feinstein (1991, A&AS, 87, 383) in front of NGC 5606 has any physical entity. From Polarimetric data we have found at least two dust layers along the line of sight to the open cluster. The observations show that both dust layers have their local magnetic field with an orientation which is close to the direction of the Galactic Plane (θ = 70°.0), but the direction of the Polarimetric vector for the members of the cluster seems to be lower than this value. NGC 5606 can be polarimetrically characterized with Pmax = 2.97% and θv, = 63°5. The internal dispersion of the polarization values for the members of NGC 5606 seems to be compatible with intracluster dust. We were able to add four possible new members to the list of stars in NGC 5606, and to reject others accepted as members in past investigations; and we identified 17 (out of the 54 observed stars) with intrinsic polarization in their light. The group of late B- and A-type stars could be physically related, with characteristics of an open cluster of intermediate age (between 0.79 and 1. × 10° yr). For this group we obtained representative values of P = 2.12% and θv = 70°.9. The new cluster, which we have provisionally named Anon (La Plata 1), extends from NE to SW across the face of NGC 5606 covering about 10′. The fitting procedure of Schmidt-Kaler's ZAMS (1982, in Landolt/Bornstein, Neue Series VI/2b) was used to derive the distance to the group, obtaining a distance modulus of Vo - Mv = 9.90 (649 pc from the Sun). The mean color excess associated with the small group is EB-V = 0.27 ± 0.08 mag and the dust distribution shows great variability across its face. We think that the small open cluster has gone undetected due to the lack of bright member stars in it.